Income Tax Penalties and the Doctrine of Punishment - Van Der Merwe, Juanita (Department of Finance and Tax, 2019)
This dissertation explores the penalty regime provided for in the Tax Administration Act, No 28 of 2011 (‘the Admin Act’), and implementation thereof in certain circumstances and behaviour on the part of the taxpayer. Even though the Admin Act has been in force for some years already, it remains necessary and relevant to explore the penalty regime that is operative to understand and confirm the scope and application thereof in various circumstances. As one discusses the different types of penalties chargeable in terms of the Admin Act it becomes evident how sternly it can be applied. Furthermore, the dissertation investigates how burdensome the regime can be and what remittance regime is available to taxpayers if they are penalised. This dissertation attempts to define what the objects of the Admin Act’s penalty regime are, and to determine whether these objectives are being achieved with the application of the penalty regime that is currently operative in the Admin Act. It also considers whether the identified objects of the Admin Act’s penalty regime accord with the doctrine of punishment. It is imperative that legislation is aligned with the objective of the penalty regime as misalignment will prejudice taxpayers, whilst potentially derogating from the purpose that the legislation seeks to achieve. In this dissertation, the crux of the penalty regime is investigated and highlighted. It also endeavours to assess the powers entrenched in the Admin Act and the need for clarification on a few uncertainties. The findings of this research study have revealed that: • The enactment of the penal provisions in the Admin Act only partially achieves the philosophy of the doctrine of punishment and, • In instances where the penal provisions do achieve the objects of punishment, it appears that the application thereof is not consistently applied in practice. The penal levying system in the Admin Act has been an improvement on the past penalty provisions as is evident in Chapter 3. However, despite the more favourable and fair outcome achieved by the penal provisions in the Admin Act, the research concludes that more specific guidance and measures in respect of the application of the penal provisions are necessary. The behaviours listed in the understatement penalty percentage table are not defined and creates the need for further improvement. Though changes have been made since the implementation thereof it still requires further revisions. In respect of inconsistent application of the penal provisions in practice it is recommended that the administrators of the legislation be better equipped in respect of the application of the penal provisions or that the processes should be changed to address the misalignment of the application of the penal provisions.